Differences in Diameter of the Growth Inhibition Zone of Klebsiella pneumonia Bacteria After Incubation at 37°C and 25°C - Juwy Trianes; Bastian Bastian; Dewi Hartati (Universitas Nahdlatul Ulama Surabaya, 2022)
Pneumonia is an infection that causes the largest death in children worldwide (South Sumatra Province), which occupies the 6th position. One of the laboratory re-identification of Klebsiella pneumonia is a multi-antibiotic testing. The high sensitivity antibiotic that is still used is amikacin. The uniqueness of the diameter of the inhibition zone using the antibiotic amikacin is that it is active against most gram-negative bacilli. But one of the several factors that affect the diameter of the inhibition zone is the incubation temperature. The optimum temperature for pathogenic bacteria is 37oC by using an incubator; however, several factors in the use of instruments such as frequent instability and disruption of installation lead to a need of incubation at 25oC. The study aimed to determine the difference in the diameter of the growth inhibition zone of K. pneumoniae after incubation at 37oC and 25oC. This research is an experimental research conducted at the Microbiology Laboratory of IKesT Muhammadiyah Palembang. The sample is K. pneumoniae which will be subjected to gram staining, biochemical tests, followed by a sensitivity test on Mueller Hinton media which is given an amikacin antibiotic disk and incubated at 370C and 250C in order to calculate the diameter of the zone of inhibition for the growth of K. pneumoniae bacteria. The data was analyzed using the alternative Wilcoxon test which obtained a p value of 0.014. The results of this investigation showed that K. pneumoniae incubated at 37°C and 25°C had a significantly different diameter of the growth inhibition zone.